Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Pelanggan Pada Starbucks Supermall Karawaci - Heri Mardiyanto; Suworo Suworo (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of Service Quality (X1) and Location (X2) on Customer Satisfaction (Y) at Starbucks Supermall Karawaci. The method used is quantitative. The sampling technique uses the Slovin formula and obtained a sample of 100 respondents. The data analysis methods used are validity test, reliability test, classical assumption test, regression test, correlation coefficient test, determination coefficient test and hypothesis test. The results of this study indicate that Service Quality has a significant effect on Customer Satisfaction with the hypothesis test obtained a tcount value > ttable, namely (5.313 > 1.984) thus the hypothesis is accepted. Location has a significant positive effect on Customer Satisfaction with the hypothesis test obtained a tcount value > ttable, namely (2.381> 1.984) thus the hypothesis is accepted. Service Quality and Location have a significant positive effect simultaneously on Customer Satisfaction with the hypothesis test obtained a calculated F value > F table, namely (409,568 > 3,090) thus the hypothesis is accepted meaning there is a significant influence between Service Quality and Location on Customer Satisfaction at Starbucks Supermall Karawaci. Keywords: Service Quality, Location, Costumer Satisfaction